Sequencing and analysis of the Meq oncogene of MDV causing marek’s disease in Bac Ninh province from 2019 to 2022 - Thanh Huong, Doan Thi; Thu Hien, Nguyen Thi; Roan, Do Thi; Minh Duc, Luu; Hue, Le Thi; Thanh Hoa, Le; Kim Xuyen, Le Thi; Khue, Nguyen Thi (Vietnam Journal of Biotechnology, 2023)
Marek’s disease is a contagious avian viral disease that is caused by a Marek’s disease virus serotype 1 (MDV-1) or gallid herpesvirus 2 (GaHV-2), a member of the genus Alphaherpesvirus, family Herpesviridae. Up to now, the disease has caused significant losses to the chicken farming industry in many provinces and cities across the country. In this study, four MDV-1 (GaHV-2) strains causing the disease in Bac Ninh province during the 2019–2022 period were identified by multiplex Polymerase Chain Reaction (PCR). Subsequently, the segments of 1020 bp encoding 339 amino acids of Meq gene (Marek’s disease virus EcoRI fragment Q) from four samples were collected and sequenced. The rate of identity and homology between the four Vietnamese strains and other global strains ranged from 89.4% to 100% and 87.6% to 100%, respectively. These rates were higher between the four Vietnamese strains and MDV-1 Chinese strains, ranging from 99.2% to 100% and 98.2% to 100%, respectively. The molecular characterization of the Meq gene revealed that all four of the GaHV-2 strains infecting chickens in the Bac Ninh province belonged to the highly virulent group, with a low proline ratio in Meq protein (ranging from 20.59–21.18%), consisting of three PPPP motifs and three interrupted motifs that contain mutations at the second position of the proline rich region (PRR): PPPP>P (Q/A/R)PP. Overall, this study provides valuable information on molecular characteristics of MDV-1 strains in Bac Ninh province during the 2019–2022 period.